Assessment of the effects of epidural labour analgesia on the second stage of labour - Khatun, Marufa; Siddique, Sharmina; Sultana, Rawshan Ara; Yasmin, Dilruba; Rahman, Tamanna; Akter, Asma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The second stage of labour is very important when the actual delivery of the baby takes place. This study aimed to evaluate the effects of epidural labour analgesia on the second stage of labour. Methods: This quasi-experimental study was carried out in Dhaka Medical College Hospital, for one-year period from July 2021 to June 2022 after ethical approval. A total of 100 admitted pregnant women (37 weeks to 41 weeks) in labour ward were included in the study according to the inclusion and exclusion criteria. Among them 50 women were in group A (with epidural analgesia) and another 50 women were in group B (without epidural analgesia). A detailed history and thorough clinical examination were carried out in each patient. Data were collected in separate case-record form and analyzed by SPSS 24. Results: Mean age, gestational age, parity were statistically similar in both Group A and Group B. Duration of second stage of labour (52.18±37.72 versus 46.2±31.42 minutes, p=0.499) in nulliparous and (34.65±21.17 versus 29.2±14.72 minutes, p=0.364) in multiparous women was comparable in the two groups. Besides, both Group A and Group B had statistically similar APGAR score at 1st (8.66±0.87 and 8.80±0.83 respectively, p=0.414) and 5th minute (9.66±0.68 and 9.74±0.59 respectively, p=0.537). Conclusions: Epidural labour analgesia can be safely recommended as a method of pain relief during labour, provided the necessary conditions are met. It does not have a significant adverse effect on the duration of the second stage of labour.